Romeo & Juliet - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Plays., 2005)
Presents a guide to Shakespeare's "Romeo and Juliet", including text and audio from various productions and preformances that provide a context for the play and its characters. Includes audio CD.